A SUBMARINE FAN IN THE AMUNDSEN BASIN, ARCTIC OCEAN - Kristoffersen Y.; Sorokin M.Y.; Jokat W.; Svendsen O. (My University, 2004)
Seismic reflection data from drifting ice stations and an icebreaker survey document the presence of a submarine fan along the east flank of the Lomonosov Ridge in the Amundsen Basin, Arctic Ocean. The fan extends from a source area at the North Greenland and Canadian Arctic continental margin to the North Pole. The fan probably developed in response to the combined effect of increased glacial sediment input during the Plio^Pleistocene and topographically confined transport of glacial debris in the deep sea passage between Lincoln Sea margin and the southern end of the Lomonosov Ridge. 4 2004 Elsevier B.V. All rights reserved.
Keywords: Arctic Ocean; Amundsen Basin; bottom features; submarine fan; glaci-marine sedimentation